PENTINGNYA AKUNTANSI RUMAH TANGGA DALAM MENINGKATKAN HIDUP ISLAMI - mulyani, sri; budiman, nita andriyani (EQUILIBRIUM, 2018)
This study aims to gather information about the importance of household accounting in improving Islamic life by looking at accounting practices carried out by informants and multiplying the benefits obtained by informants in carrying out accounting practices in their households. The method used is a qualitative method with a phenomenological approach. The informants in this study were eight seventh semester accounting students who had a family. Data collection techniques were carried out by in-depth interviews with each informant. The results of this study explain that the informants all carry out accounting practices in their household since they are married and recorded by the wife. Of all the informants stated that accounting in the household is important for the reasons: 1) can create calm in financial management, 2) form a person who is thrifty and careful, 3) can be used as an evaluation and long-term decisions to save, and 4 ) as an afterlife investment decision to pay zakat and shodaqah.